1996
DOI: 10.1159/000217193
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of the Low Molecular Weight Heparin Tinzaparin in Haemodialysis

Abstract: Fifty-two patients with chronic renal failure undergoing hospital haemodialysis were given a single bolus dose of tinzaparin (Innohep, Leo Laboratories, UK) into the arterial side of the dialyser, for up to 43 consecutive dialyses. The mean tinzaparin dose at the beginning was 2,139 IU anti-Xa and at the end 2,186 IU anti-Xa. Overall, tinzaparin proved a satisfactory anticoagulant for 1,370 (96.0%) out of 1,427 dialyses. Significant clot formation was prevented in 1,326 (92.8%) out of 1,429 dialyses. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
5
11
0
Order By: Relevance
“…Our findings are in line with those obtained with tinzaparin [28]. The serum FPA concentration and the anti-FXa action follows an inverse trend.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are in line with those obtained with tinzaparin [28]. The serum FPA concentration and the anti-FXa action follows an inverse trend.…”
Section: Discussionsupporting
confidence: 92%
“…Like previous reports [28, 29, 30, 31, 32, 33, 34]based on a short-term follow-up, our study confirms that adequate and safe anticoagulation levels may be achieved with LMWH during hemodialysis together with a low risk of bleeding. This was so whether we used a PS low-flux or PS high-flux membrane.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also showed that the changes of APTT and plasma antithrombin activity were not sensitive enough for monitoring serum LMWH activity. These results are comparable with those obtained in previous studies with higher LMWH dosages [4, 5]. …”
Section: Discussionsupporting
confidence: 92%